Cardiac Tumor in Newborn as the Marker of Tuberous Sclerosis: Clinical Case - Elena I. Naumenko; Valeria G. Anufrieva; Irina A. Grishutkina (Union of pediatricians of Russia, 2020)
Background. The most common cardiac tumor in children is rhabdomyoma. Its frequency is 58.3% in the early neonatal period. Rhabdomyoma is associate with tuberous sclerosis pretty often (50-86% of all cases) and it be its diagnostic marker.Clinical case description. This article presents case study of the newborn from the mother with burdened obstetric and gynecological anamnesis, type 1 diabetes, nicotine addiction. Multiple mass lesions were revealed in the child's heart on the 31 st week of gestation. On examination: systolic murmur over the heart region, fibrous nodules on the skin all over the body up to 1-5 mm in diameter, indurated on palpation. Diagnosed echocardiographically: multiple attached, round masses were revealed in the cavity of left ventricle of 7.9×4.1 mm in size, in outflow track of left ventricle (near the aortic root) - 9.3×4.8 mm, in the cavity of right ventricle - 4.3×3.2 mm, in the cavity of right auricle - 5.1×5.0 mm. Pathologic activity of cardiac conduction system was presented only by single supra-ventricular and ventricular extrasystoles due to the results of 24-hour monitoring.Conclusion. Children with cardiac rhabdomyoma diagnosed in prenatal period are threatened by tuberous sclerosis, thus, complex dynamic observation and molecular genetic testing is needed.